Assessing Students’ Level of Mastering the Federal Component of the State Educational Standard in the English and the Russian Languages in Russia - Vasilyevna Badelina, Mariya; Yuryevna Orekhova, Elena (International Journal of Engineering and Technology, 2018)
The purpose of the article is to consider the system of assessing the level of graduatesâ€™ mastering the Federal Component of the State Educational Standard in the Russian Federation. The stated problem has been the subject of efficient research since the moment of introducing the Unified State Exam (USE) in Russia in 2005. The relevance of the study is determined by the fact that the assessment system is demonstrated through the comparative analysis of the similarities and differences between the (USE) in the Russian Language (native) and the English Language (foreign), carried out by the authors. Lately the number of students taking both an exam in Russian and English has been increasing and according to this the content and tasks in both exams have been modified. The authors describe the forms of the State Final Certification (SFC) for the English and the Russian Languages, participants, terms and duration, requirements for the USE, means of communication during the SFC, procedures for checking examination works and others. The reveals that there is a significant similarity between two types of examinations and learning both the Russian and English Languages is really important that is primarily due to the modern trends in the development of Russian society.Â Â Â